''Strathcona'' (1920)
The schooner ''Strathcona'' in the waters off Newfoundland. This collection features an album of 152 black and white photographs of the Grenfell Mission hospital and staff at St. Anthony, on Newfoundland's Great Northern Peninsula, taken in the 1920s-30s. A small number of photos feature other locations. It is unknown who took the photographs; the album owner was most likely a Mission nurse.